Relationship between mathematics statistics engagement and attitudes towards statistics among undergraduate students in Malaysia - Salim, Nur Raidah; Mohd Ayub, Ahmad Fauzi (AIP Publishing LLC, 2016)
This paper explored the relationship between the attitudes toward statistics and mathematics statistics engagement among undergraduate students taking the statistic course. A total of 293 undergraduate students from several programs at Universiti Putra Malaysia (UPM) were the sample of the study. A structured, self-administered questionnaire was used to elicit responses from these students. Descriptive analyses showed the overall mean for students’ mathematics statistics engagement was 3.38 (SD = .36). The analysis on mathematics statistics engagement domains revealed behavioural engagement had the highest mean (M = 3.63, SD = .52), followed by affective engagement (M = 3.35, SD = .41) and cognitive engagement (M = 3.26, SD = .35). Inferential analysis indicated attitudes towards statistic were positively related to mathematics statistics engagement (p = .721**, p = .001). Further analysis on mathematics statistics engagement domain indicated attitudes towards statistics were positively related to the affective domain (p = .902**, p < 0.001), cognitive domain (p = .818**, p < 0.001) and behavioral domain (p = .855**, p < 0.001). These findings show attitudes are important for students to be engaged in mathematics statistics. Implications of the findings are discussed.